Electronic, structural, and hyperfine properties of pure and Cd-doped hexagonal La2O3 semiconductor - Richard, Diego (2015)
We present a detailed first-principles study of structural, electronic, and hyperfine properties of pure and Cd-doped lanthanum sesquioxide (La2O3) with the hexagonal structure (A-phase). We calculated the equilibrium structure, the density of states (DOS), the energy band-gap and, finally, the electric-field-gradient (EFG) tensor at the different atomic sites (La, O, and Cd at substitutional La sites) using different approximations for the exchange and correlation potential. In the case of pure A-La2O3 our predictions are compared with available experimental data obtained in X-ray Diffraction experiments and Nuclear Quadrupole Resonance and Nuclear Magnetic Resonance spectroscopies. The excellent agreement between theory and experiments gave us a solid base for the study of Cd-doped A-La2O3. In the case of the doped system, a very good agreement between the predicted and the experimental EFG at the 111Cd sites (obtained in Time-Differential Perturbed γ-γ Angular Correlations experiments) was found. From the comparison of the EFGs obtained at different probe sites we can discuss and elucidate the role played by the electronic structure of the probe atoms, and the structural and electronic modifications induced by the Cd impurity in the La2O3 host, on the origin of the EFG.